THE EFFECT OF COMPETENCE ON JOB READINESS WITH WORK MOTIVATION AS A MEDIATOR: A STUDY ON GENERATION Z IN JABODETABEK - Agustina, Neysa; Turangan, Joyce A. (International Journal of Application on Economics and Business, 2025)
Generation Z, also known as the post-millennial generation is the pioneering generation to grow up in an era heavily influenced by technology. This study aims to explore the effect of competence on job readiness, with work motivation as a mediating variable among Generation Z in the Jabodetabek area. A quantitative approach was used, involving a survey of 180 respondents selected through probability sampling with a simple random method. The data were obtained using questionnaires and analyzed through Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results show that both competence and work motivation have a positive and significant impact on job readiness. Furthermore, competence has a positive and significant effect on job readiness through work motivation as a mediator. This study is motivated by the low level of job readiness in Indonesia due to skill mismatches, largely influenced by the rapid technological advancements affecting Generation Z. The findings offer important insights for companies in developing more effective recruitment and training strategies to improve job readiness among Generation Z.